The Effect of Preoperative Health Education with Educational Video Media on Anxiety, Pain, and Early Mobilization Behavior in Patients with Postoperative Lower Extremity Fracture – ORIF (Open Reduction Internal Fixation) - Haris Listyawan; Yuly Peristiowati; Rahmania Ambarika (Health and Technology Journal (HTechJ), 2026)
Surgical interventions experience various challenges during the recovery process, including levels of anxiety, pain, and difficulty in early mobilization. The provision of education as a health education method needs to be emphasized in this phase. The sophistication of technology in presenting health education through video media is one alternative for education delivery. This study aims to explain the effect of preoperative health education with educational video media on anxiety, pain, and early mobilization behavior in patients with post-ORIF (Open Reduction Internal Fixation) lower extremity fractures. This study uses an Experimental Design (posttest-only with a control group). Two groups were randomly selected; the experimental group received a health education intervention using educational videos, while the control group received a health education intervention in accordance with the hospital's Standard Operating Procedures (SOPs). Analysis with an Independent sample t-test showed a significant value of intervention in providing preoperative health education with educational video media on anxiety (p < α = 0.040), on pain (p < α = 0.025), and on early mobilization (p < α = 0.001) in patients with post-ORIF (Open Reduction Internal Fixation) lower extremity fractures. Preoperative health education using an educational video on early mobilization behavior variables showed a difference or average change value that was more positive than those for the anxiety and pain variables. Preoperative health education intervention with educational video media affects anxiety, pain, and early mobilization of patients with lower limb fractures after ORIF. The delivery of education with video media is more effective and more focused on achieving the goal of providing education. The intervention group showed a decrease in the average level of anxiety and pain, as well as a better average early mobilization behavior than the control group. Health education in the form of educational videos attracts more attention by delivering clearer information supported by the detailed process of moving illustrations and presenting objects in detail, which can help understand difficult material and provide an emotional and motivational impact, to help respondents reduce anxiety levels, pain, and improve early mobilization behaviors in the rehabilitation phase after surgery.